KONSEP PENANGANAN MASALAH KECELAKAAN LALU-LINTAS - Hikmat Iskandar (Jurnal Jalan-Jembatan, 2006)
Since three last decades, number of traffic accidents in Indonesia have not yet been showing a significant reduction, although Police reported a decrease trend in number. In year 1971, 23294 occurences have been reported and decreased to 13399 in year 2003. However, Index Fatality is still high, it was 11.9% in year 1971 and increased up to 39.9% in year 1996 and tends to increase if there is no real action to stop the growth. It warned travellers by high probability of their involvement in an accident, five out of 10,000 vehicle ownership, are regressed involved in an accident and four out of ten of victims are of fatals. In order to overcome the problem, an accident reduction program has been setup and to be implemented, started from North Sumatra Corridor (North Sumatra, Riau, West Sumatra, and Aceh provinces) and Bali and to be continue to other provinces. This paper aims to present a conceptual back ground of this traffic accident reduction program, covering organization under related institution to be developed in the region, a coordination model, traffic accident investigation unit, and practical technology needed and applied.